Theories of self-regulation - Fletcher, A (1993)
Self-regulation is becoming more and more prevalent in the UK, yet there has been very little theoretical examination of the issues involved. This thesis aims to fill that gap. The main intuition examined is that self-regulation will be a feasible form of regulation only if there exists some state, attainable via some form of regulation, which raises both industry profits and total social welfare, relative to the latssez faire. Modelling self-regulation thus involves finding situations in which the laissez faire is not welfare-optimal; in which sellers can improve upon their profits, relative to those at the laissez fafre; and in which this profit-improvement happens also to raise total social welfare. Such situations may exist when there is asymmetric information between sellers and consumers and/or externalities. Chapter 3 examines quality choice under hidden irreversible action, It is shown that any comparison between the welfare under self-regulation and that under laissez faire will turn on the relative signs and values of (a) the net between-seller externality; (b) the difference in quality valuations between marginal and infra-marginal consumers; and (c) the effect of quality choice on total output. Under certain circumstances, however, self-regulation will certainly be the welfare-superior. Chapter 4 examines quality choice under moral hazard. Self-regulation is shown to be feasible. It is also compared with external regulation: If qualities are observable (with a lag) but not verifiable, an SRO may have an advantage over an external regulator in that an SRO can condition its regulation on quality. Self-regulation in fact becomes more likely to be welfare-superior to external regulation (a) as fraud becomes more important relative to cheating on quality; (b) as sellers become more homogeneous in terms of capital; and (c) as the observation lag becomes greater. Chapter 5 considers the factors that might influence the optimal number of SROs in an industry.